Compromise of Second-Line Antiretroviral Therapy Due to High Rates of Human Immunodeficiency Virus Drug Resistance in Mozambican Treatment-Experienced Children With Virologic Failure. (25th October 2018) - Vaz, Paula; Buck, W Chris; Bhatt, Nilesh; Bila, Dulce; Auld, Andrew; Houston, James; Cossa, Loide; Alfredo, Charity; Jobarteh, Kebba; Sabatier, Jennifer; Macassa, Eugénia; Sousa, Amina; et al.
Abstract: Background: Virologic failure (VF) is highly prevalent in sub-Saharan African children on antiretroviral therapy (ART) and is often associated with human immunodeficiency virus drug resistance (DR). Most children still lack access to routine viral load (VL) monitoring for early identification of treatment failure, with implications for the efficacy of second-line ART. Methods: Children aged 1 to 14 years on ART for ≥12 months at 6 public facilities in Maputo, Mozambique were consecutively enrolled after informed consent. Chart review and caregiver interviews were conducted. VL testing was performed, and specimens with ≥1000 copies/mL were genotyped. Results: Of the 715 children included, the mean age was 103 months, 85.8% had no immunosuppression, 73.1% were taking stavudine/lamivudine/nevirapine, and 20.1% had a history prevention of mother-to-child transmission exposure. The mean time on ART was 60.0 months. VF was present in 259 patients (36.3%); 248 (95.8%) specimens were genotyped, and DR mutations were found in 238 (96.0%). Severe immunosuppression and nutritional decline were associated with DR. M184V and Y181C were the most common mutations. In the 238 patients with DR, standard second-line ART would have 0, 1, 2, and 3 effective antiretrovirals in 1 (0.4%), 74 (31.1%), 150 (63.0%), and 13 (5.5%) patients, respectively. Conclusion: This cohort had high rates of VF and DR with frequent compromise of second-line ART. There is urgent need to scale-up VL monitoring and heat-stable protease inhibitor formulations or integrase inhibitorsfor a more a durable first-line regimen that can feasibly be implemented in developing settings.